Human Milk Analysis Using Mid-Infrared Spectroscopy. (April 2016) - Groh-Wargo, Sharon; Valentic, Jennifer; Khaira, Sharmeel; Super, Dennis M.; Collin, Marc
Background: The composition of human milk is known to vary with length of gestation, stage of lactation, and other factors. Human milk contains all nutrients required for infant health but requires fortification to meet the needs of low-birth-weight infants. Without a known nutrient profile of the mother's milk or donor milk fed to a baby, the composition of the fortified product is only an estimate. Human milk analysis has the potential to improve the nutrition care of high-risk newborns by increasing the information about human milk composition. Equipment to analyze human milk is available, and the technology is rapidly evolving. This pilot study compares mid-infrared (MIR) spectroscopy to reference laboratory milk analysis. Methods : After obtaining informed consent, we collected human milk samples from mothers of infants weighing <2 kg at birth. Duplicate samples were analyzed for macronutrients by MIR and by reference laboratory analysis including Kjeldahl for protein, Mojonnier for fat, and high-pressure liquid chromatography for lactose. Intraclass correlation coefficients, Bland-Altman scatter plots, and paired t tests were used to compare the two methods. Results : No significant differences were detected between the macronutrient content of human milk obtained by MIR vs reference laboratory analysis. Conclusions : MIR analysis appears to provide an accurate assessment of macronutrient content in expressed human milk from mothers of preterm infants. The small sample size of this study limits confidence in the results. Measurement of lactose is confounded by the presence of oligosaccharides. Human milk analysis is a potentially useful tool for establishing an individualized fortification plan.